2016
DOI: 10.1097/pcc.0000000000000983
|View full text |Cite
|
Sign up to set email alerts
|

PICU Up!: Impact of a Quality Improvement Intervention to Promote Early Mobilization in Critically Ill Children*

Abstract: Objective To determine the safety and feasibility of an early mobilization program in a pediatric intensive care unit (PICU). Design Observational, pre-post design. Setting PICU in a tertiary academic hospital in the United States. Patients Critically ill pediatric patients admitted to the PICU. Intervention This quality improvement project involved a usual-care baseline phase, followed by a quality improvement phase that implemented a multicomponent, interdisciplinary, and tiered activity plan to prom… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
126
0
5

Year Published

2017
2017
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 157 publications
(135 citation statements)
references
References 31 publications
4
126
0
5
Order By: Relevance
“…Prior work examining pediatric rehabilitation within the PICU has focused primarily on understanding trends in service use 1,35 and exploring barriers to and safety of implementing rehabilitation services within the PICU. 36 These studies found rehabilitation services are feasible within the PICU, and approximately 50% of the PICU population receives rehabilitation services. To our knowledge, this is the first study to examine the association between receiving early rehabilitation services and caregiver stress in any population.…”
Section: Discussionmentioning
confidence: 99%
“…Prior work examining pediatric rehabilitation within the PICU has focused primarily on understanding trends in service use 1,35 and exploring barriers to and safety of implementing rehabilitation services within the PICU. 36 These studies found rehabilitation services are feasible within the PICU, and approximately 50% of the PICU population receives rehabilitation services. To our knowledge, this is the first study to examine the association between receiving early rehabilitation services and caregiver stress in any population.…”
Section: Discussionmentioning
confidence: 99%
“…Mobility programs expedite return to activities of daily living and reduce lengths of stay and cost, without affecting safety events, but they have not been adequately prospectively studied in children 10,25,26 . A single center quality initiative has shown that mobility interventions for critically ill children can be increased without negative safety effects 19 .…”
Section: Discussionmentioning
confidence: 99%
“…Small pediatric studies highlight the uncertainties and challenges of incorporating rehabilitative services into clinical PICU practice while other centers are translating data from adult studies into pediatric practice 13–15 . There is a vital need for prospective interventional trials in critically ill children to inform guidelines for the optimal consultation for physical (PT) and occupational therapy (OT) and other rehabilitative and supportive services to demonstrate efficacy in improving outcome 13,15–19 .…”
Section: Introductionmentioning
confidence: 99%
“…Recently, pediatric intensive care early mobility and rehabilitation initiatives such as "PICU Up!" also show promise for improving functional survival (22). Interestingly, the majority of these types of studies have not reported baseline light and sound characteristics, nor have they demonstrated whether bundle or mobility interventions inherently alter environmental characteristics, and if this aspect is uniquely beneficial.…”
Section: Introductionmentioning
confidence: 99%